Risk for incident comorbidities, nonhepatic cancer and mortality in acute hepatic porphyria: A matched cohort study in 1244 individuals. Issue 2 (30th December 2022) - Lissing, Mattias; Vassiliou, Daphne; Floderus, Ylva; Harper, Pauline; Yan, Jacinth; Hagström, Hannes; Sardh, Eliane; Wahlin, Staffan
Abstract: The acute hepatic porphyrias (AHP) are associated with long‐term complications such as primary liver cancer, hypertension, and chronic kidney disease. Data on other related comorbidities are scarce. In this register‐based, matched cohort study, we assessed the risks of nonhepatic cancers, cardiovascular diseases, renal diseases, psychiatric disorders, and mortality in relation to porphyria type, sex, and biochemical disease activity. All patients in the Swedish porphyria register with a verified AHP diagnosis during 1987–2015 were included. The biochemical activity of acute intermittent porphyria was assessed using recorded maximal urinary porphobilinogen (U‐PBG). Data on incident comorbidities and mortality were collected from national health registries. Cumulative incidences, rates, and hazards were compared to reference individuals from the general population, matched 1:10 by age, sex, and county. We identified 1244 patients with AHP with a median follow‐up of 19 years. Health registries identified 149 AHP‐subjects (12.0%) with nonhepatic cancer, similar to 1601 (13.0%) in the matched reference population ( n  = 12 362). Patients with AHP had a higher risk of kidney cancer (0.8% vs. 0.2%, p  < 0.001), hypertension, and chronic kidney disease but no increase in risk for cardiovascular disease, except for cerebrovascular disease in patients with elevated U‐PBG, (aHR = 1.40 [95% CI:1.06–1.85]). Mortality risk during follow‐up was higher among patients with AHP (21% vs. 18%, p  = 0.001), and associated with primary liver cancer, female sex, and biochemical activity. In conclusion, AHP is associated with an increased risk of kidney cancer, hypertension, chronic kidney disease, and mortality but not with cardiovascular disease or other nonhepatic cancers.